2019
DOI: 10.26466/opus.530330
|View full text |Cite
|
Sign up to set email alerts
|

Okul Öncesi Öğretmenlerinin Öz Yeterlik İnançlarının Bazı Değişkenlere Göre İncelenmesi

Abstract: The aim of this study is to determine whether the self-efficacy beliefs of teachers who work as preschool teachers in different institutions differ according to factors gender, age, professional experience and the type of institution. The study group consisted of 108 preschool teachers working in the city center of Konya. Data collection tools were "Demographic Information Form" developed by the researcher, and "Self-efficacy Beliefs Scale of Preschool Teachers" developed by Tepe and Demir (2012). The data of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…When looking at the other findings from the study, no relationship was found between educators' self-efficacy beliefs and age. In Kaya's (2019) study on teachers' self-efficacy, no significant relationship was found between age and self-efficacy. Again, in the study of Yılmaz and Çokluk Bökeoğlu (2008), it was found that there was no difference between age and self-efficacy beliefs.…”
Section: Discussion and Resultsmentioning
confidence: 83%
“…When looking at the other findings from the study, no relationship was found between educators' self-efficacy beliefs and age. In Kaya's (2019) study on teachers' self-efficacy, no significant relationship was found between age and self-efficacy. Again, in the study of Yılmaz and Çokluk Bökeoğlu (2008), it was found that there was no difference between age and self-efficacy beliefs.…”
Section: Discussion and Resultsmentioning
confidence: 83%
“…In their study on students in the department of computer and instructional technology education, Akkoyunlu and Orhan (2003) stated that self-efficacy levels increased with increasing age. In a study conducted on preservice preschool teachers, Kaya (2019) stated that those aged 41 and over had higher selfefficacy levels than the 36-40 age group, the 36-40 age group had higher self-efficacy levels than the 31-35 age group, and the 31-35 group had higher self-efficacy levels than the 26-30 age group. It was found that self-efficacy levels increased with increasing age.…”
Section: Discussionmentioning
confidence: 99%
“…Hizmet öncesi daha çok pedagojik bilgiye odaklanma eğilimi (Liaw, 2009), öğrenci sayısının fazlalığı, öğretim elemanı yetersizliği, öğretim elemanlarının niteliği, mezun olan öğretmen adaylarının istihdam sorunları, öğretmenlik mesleğine bakış açısı gibi konularda birtakım problemler bulunmaktadır (Şendağ ve Gedik, duygusunun artığı (Palmer, Stough, Burdenski ve Gonzales, 2005;Wolters ve Daugherty, 2007) veya mesleki deneyim artıkça öğretmenlerin yeterlilik duygularının değişmediği yönünde çalışmalarda mevcuttur. (Kaya, 2019;Zee, Koomen, Jellesma, Geerlings ve de Jong, 2016;Yılmaz, Çokluk-Bökeoğlu, 2008).…”
Section: Araştırma Grubuunclassified